(untitled) (Clinics, 2013)
Aspermatogenesis is a severe impairment of spermatogenesis in which germ cells are completely lacking or present in an immature form, which results in sterility in approximately 25% of patients. Because assisted reproduction techniques require mature germ cells, biotechnology is a valuable tool for rescuing fertility while maintaining biological fatherhood. However, this process involves, for instance, the differentiation of preexisting immature germ cells or the production/derivation of sperm from somatic cells. This review critically addresses four potential techniques: sperm derivation in vitro, germ stem cell transplantation, xenologous systems, and haploidization. Sperm derivation in vitro is already feasible in fish and mammals through organ culture or 3D systems, and it is very useful in conditions of germ cell arrest or in type II Sertoli-cell-only syndrome. Patients afflicted by type I Sertoli-cell-only syndrome could also benefit from gamete derivation from induced pluripotent stem cells of somatic origin, and human haploid-like cells have already been obtained by using this novel methodology. In the absence of alternative strategies to generate sperm in vitro, in germ cells transplantation fertility is restored by placing donor cells in the recipient germ-cell-free seminiferous epithelium, which has proven effective in conditions of spermatogonial arrest. Grafting also provides an approach for ex-vivo generation of mature sperm, particularly using prepubertal testis tissue. Although less feasible, haploidization is an option for creating gametes based on biological cloning technology. In conclusion, the aforementioned promising techniques remain largely experimental and still require extensive research, which should address, among other concerns, ethical and biosafety issues, such as gamete epigenetic status, ploidy, and chromatin integrity.